Long-term impacts of parliamentary gender quotas in a single-party system: Symbolic co-option or delayed integration? - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2018)
In recent years scholars have shifted their attention from the causes behind parliamentary gender quotas to their consequences for women’s descriptive, substantive, and symbolic representation. We contribute to this literature by focusing on long-term effects of gender quotas in the context of an authoritarian one-party system. Here we contest dominant theoretical explanations which posit that gender quotas in authoritarian states primarily serve the goals of symbolic co-option and window-dressing. Rather, we argue that while authoritarian adaptation may motivate the introduction of gender quotas, these quotas may result over time in what we call a delayed integration process featuring a gradual rise of women into arenas of power alongside increasing professionalization and capabilities of women within parliament. This argument is tested and supported via a 72-year longitudinal analysis of over 6000 female and male representatives of the Vietnamese National Assembly, a single-party parliament with long-standing gender quotas.